2017
DOI: 10.1007/s10802-017-0380-8
|View full text |Cite
|
Sign up to set email alerts
|

Like Father, like Child: Early Life Family Adversity and Children’s Bullying Behaviors in Elementary School

Abstract: Family adversity has been associated with children’s bullying behaviors. The evidence is, however, dominated by mothers’ perceptions of the family environment and a focus on mothers’ behaviors. This prospective population-based study examined whether children’s bullying behaviors were associated with mother- and father-reported family adversity, assessed before and after child birth. Peer-nominations were used to assess bullying behaviors of 1298 children in elementary school (mean age 7.5 years). The followin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 71 publications
1
6
0
2
Order By: Relevance
“…Fathers’ harsh parenting increased the odds of being a perpetrator, but we did not find this relation for mothers. Our findings are consistent with studies that reported relations between negative and harsh parenting and increased child aggression and bullying (de Vries et al, 2018 ; Nocentini et al, 2019 ), as well as studies that found effects for fathers’ (but not mothers’) harsh parenting on aggression (Chang et al, 2003 ) and cyberbullying (Zurcher et al, 2018 ). The finding that inhibitory control problems increased the odds of being a perpetrator is consistent with previous reports on inhibitory control being related to externalizing problems (Riggs et al, 2004 ) and aggression (Raaijmakers et al, 2008 ).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Fathers’ harsh parenting increased the odds of being a perpetrator, but we did not find this relation for mothers. Our findings are consistent with studies that reported relations between negative and harsh parenting and increased child aggression and bullying (de Vries et al, 2018 ; Nocentini et al, 2019 ), as well as studies that found effects for fathers’ (but not mothers’) harsh parenting on aggression (Chang et al, 2003 ) and cyberbullying (Zurcher et al, 2018 ). The finding that inhibitory control problems increased the odds of being a perpetrator is consistent with previous reports on inhibitory control being related to externalizing problems (Riggs et al, 2004 ) and aggression (Raaijmakers et al, 2008 ).…”
Section: Discussionsupporting
confidence: 92%
“…Specifically, parental discipline provides key socializing moments for children's learning of moral reasoning and disengagement (Campaert et al, 2018 ). For example, children who receive harsh discipline after misbehaving may learn that aggression is an acceptable way to achieve a certain outcome (i.e., getting your way, de Vries et al, 2018 ). In early childhood, when children have few other social circles that could buffer against adverse modeling influences, harsh parenting is an environmental factor to which children are vulnerable and susceptible (Labella & Masten, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Economic problems, poverty [18], unemployment [19], family conflicts or adversity [20], parental mental health [21] and tobacco use [22] are also positively associated with or predictors of both internalizing and externalizing behaviors. Weak social structure and social exclusion are also breeding grounds for behavioral deviations.…”
Section: Introductionmentioning
confidence: 99%
“…He considered a bully as an aggressive and impulsive individual who requires domination (Thomas Cook 2020). About one-third of children in primary school are involved in bullying (De Vries et al 2017). Currently, 15%-30% of students are affected by bullying and its consequences (Hosseini & Rhmadrash 2020).…”
Section: Introductionmentioning
confidence: 99%